Assessment of equity in healthcare financing in Fiji and Timor-Leste: a study protocol. Issue 12 (2nd December 2014) - Asante, Augustine D; Price, Jennifer; Hayen, Andrew; Irava, Wayne; Martins, Joao; Guinness, Lorna; Ataguba, John E; Limwattananon, Supon; Mills, Anne; Jan, Stephen; Wiseman, Virginia
Abstract : Introduction: Equitable health financing remains a key health policy objective worldwide. In low and middle-income countries (LMICs), there is evidence that many people are unable to access the health services they need due to financial and other barriers. There are growing calls for fairer health financing systems that will protect people from catastrophic and impoverishing health payments in times of illness. This study aims to assess equity in healthcare financing in Fiji and Timor-Leste in order to support government efforts to improve access to healthcare and move towards universal health coverage in the two countries. Methods and analysis: The study employs two standard measures of equity in health financing increasingly being applied in LMICs—benefit incidence analysis (BIA) and financing incidence analysis (FIA). In Fiji, we will use a combination of secondary and primary data including a Household Income and Expenditure Survey, National Health Accounts, and data from a cross-sectional household survey on healthcare utilisation. In Timor-Leste, the World Bank recently completed a health equity and financial protection analysis that incorporates BIA and FIA, and found that the distribution of benefits from healthcare financing is pro-rich. Building on this work, we will explore the factors that influence the pro-rich distribution. Ethics and dissemination: The study is approved by the Human Research Ethics Committee of University of New South Wales, Australia (Approval number: HC13269); the Fiji National Health Research Committee (Approval # 201371); and the Timor-Leste Ministry of Health (Ref MS/UNSW/VI/218). Results: Study outcomes will be disseminated through stakeholder meetings, targeted multidisciplinary seminars, peer-reviewed journal publications, policy briefs and the use of other web-based technologies including social media. A user-friendly toolkit on how to analyse healthcare financing equity will be developed for use by policymakers and development partners in the region.